Role of adipokinetic hormone during starvation in Drosophila. - Mochanová, M.; Tom?ala, A.; Svobodová, Z.; Kodrík, D. (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2018)
The role of adipokinetic hormone (Drome-AKH) in maintaining the levels of basic nutrients, under starvation conditions, was studied using Drosophila melanogaster mutants with AKH deficiency (Akh1) and AKH abundance (EE-Akh). Our results showed lipids as the main energy reserve in Drosophila, and their physiological level and metabolism were shown to be under the control of AKH. AKH abundance in the body resulted in lower levels of triacylglycerols and diacylglycerols than in the controls, probably due to a more intensive metabolism; interestingly, there was a disproportional representation of fatty acids in triacylglycerols and diacylglycerols in Drosophila. Lower level of glycogen and its partial control by AKH suggest its lesser role as the storage substance. However, maintenance of free carbohydrate level in Drosophila seemed to be critical; when glycogen stores are exhausted, carbohydrates are synthesized from other sources. Protein levels and their alterations, under starvation, did not seem controlled by AKH. AKH-deficient flies were more resistant while AKH-abundant flies were more sensitive to starvation; females were found to be more resistant than males, regardless of the AKH level, probably due to higher body mass and higher amount of nutrients. However, in accordance with the level of all nutrients, that of AKH also gradually decreased with prolonged starvation.